Preparation process of metalized ceramic substrate

By preparing a metallization layer containing transition metal oxides and modified phenolic resin on the surface of the ceramic substrate and carrying out rare earth ion implantation, the problem of insufficient bonding strength between ceramics and metals is solved, and a high-strength metallization layer is realized, suitable for Various electronic devices.

CN119409519AActive Publication Date: 2025-02-11XINXING ELECTRONIC CERAMICS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411103126.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-02-11
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

Ceramics and metals cannot be welded directly, so a metallization layer that is firmly bonded to the ceramic needs to be prepared on the surface of the ceramic. How to improve the bonding strength between the metallization layer and the ceramic substrate has become the focus of research.

Method used

Using a metallized ceramic substrate preparation process, including the preparation of a metallized slurry containing transition metal oxides and a metallized slurry containing ethylene-vinyl alcohol copolymer modified phenolic resin, by printing or coating the metallized slurry On the surface of the ceramic substrate, and after drying and sintering, the bond strength is further improved by rare earth ion implantation.

Benefits of technology

By improving the bonding strength between the ceramic substrate and the metallization layer, the tensile strength of the metallization layer reaches more than 40MPa, and is suitable for LED heat dissipation substrates, ceramic packaging, electronic circuit substrates and semiconductor packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409519A_ABST
    Figure CN119409519A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic metallization, in particular to a preparation process of a metallized ceramic substrate, which comprises the following steps: firstly preparing a ceramic substrate containing transition metal oxide, then preparing metallized slurry containing ethylene-vinyl alcohol copolymer modified phenolic resin, and finally printing or coating the metallized slurry on the surface of the ceramic substrate, thereby obtaining the metallized ceramic substrate. The tensile strength of the metalized layer of the metalized ceramic substrate prepared by the method disclosed by the invention reaches more than 40MPa, and the metalized ceramic substrate has a wide application prospect in the fields of LED (Light Emitting Diode) heat dissipation substrates, ceramic packaging, electronic circuit substrates, semiconductor packaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic metallization, in particular to a preparation process of a metallized ceramic substrate. Background Art

[0002] Ceramic substrates have a series of excellent properties such as high temperature resistance, wear resistance, and good insulation. In actual production, ceramics and metals cannot be welded directly. A metallization layer that is firmly bonded to the ceramic must be prepared on the ceramic surface before welding with other metal devices can be achieved. This process is called metallization of ceramics, and the metallization layer will directly affect the final performance of the welded body. How to improve the bonding strength between the metallization layer and the ceramic substrate has become the current research focus. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a preparation process of a metallized ceramic substrate.

[0004] The technical solutions adopted are as follows:

[0005] A preparation process of a metallized ceramic substrate is as follows:

[0006] S1: preparing a ceramic substrate containing a transition metal oxide;

[0007] S2: preparing a metallization slurry containing ethylene-vinyl alcohol copolymer modified phenolic resin;

[0008] S3: Printing or coating the metallization slurry on the surface of the ceramic substrate, followed by drying and sintering.

[0009] Furthermore, the ceramic substrate is also implanted with rare earth ions.

[0010] Furthermore, the rare earth ions are lanthanum ions and / or cerium ions.

[0011] Furthermore, the transition metal oxide in S1 is any one or more combinations of nickel oxide, cobalt oxide, iron oxide or zinc oxide.

[0012] Further, the preparation method of the ethylene-vinyl alcohol copolymer modified phenolic resin in S2 is as follows:

[0013] Dissolve ethylene-vinyl alcohol copolymer in phenol aqueous solution, add formaldehyde and sodium hydroxide, stir to react for 1-5 hours, and then distill under reduced pressure to remove small molecules.

[0014] Furthermore, the reaction temperature is 50-70°C.

[0015] Further, S1 is as follows:

[0016] Alumina and transition metal oxides in a mass ratio of 80-100:1-5 are mixed and ball-milled and then dried to obtain a mixed powder, a green body is obtained by a tape casting method, the green body is debinded and sintered to obtain a ceramic substrate, and finally the ceramic substrate is implanted with rare earth ions.

[0017] Furthermore, the metallization paste includes the following components in percentage by mass:

[0018] 5-10% of ethylene-vinyl alcohol copolymer modified phenolic resin, 1-3% of ethyl cellulose, 35-45% of molybdenum powder, 8-12% of manganese powder, 10-15% of active agent, and the balance is pinene alcohol.

[0019] Further, the active agent includes calcium oxide, lanthanum oxide, silicon dioxide and titanium dioxide;

[0020] The mass ratio of the calcium oxide, lanthanum oxide, silicon dioxide and titanium dioxide is 1-5:1-5:1-5:1-5.

[0021] Furthermore, the sintering temperature in S3 is ≥ 1200°C.

[0022] Beneficial effects of the present invention:

[0023] The present invention provides a preparation process of a metallized ceramic substrate. Rare earth ion implantation into the ceramic substrate can lead to changes in the microstructure of the near-surface region of the ceramic substrate, thereby improving the bonding strength between the ceramic substrate and the metallization layer.

[0024] The ethylene-vinyl alcohol copolymer modified phenolic resin is used as an organic binder phase, which can make the metallization slurry reach a suitable viscosity range, so that it can adhere well to the surface of the ceramic substrate. In addition, it is pyrolyzed during high-temperature sintering, and carbon nanotubes are generated in situ at the interface between the ceramic substrate and the metallization layer. The carbon nanotubes can form a multi-scale branched structure to improve the physical bonding between the interfaces, thereby enhancing the bonding strength. Compared with other organic binders, the ethylene-vinyl alcohol copolymer modified phenolic resin has a higher carbon residue rate. When sintered at high temperature, it can provide more carbon-based structures and generate more carbon nanotubes. The inventors further found that adding transition metal oxides or rare earth ion implantation to the ceramic substrate can improve the bonding strength between the ceramic substrate and the metallization layer. The reason may be that the transition metal oxide has a certain catalytic effect, which promotes the generation of carbon nanotubes when the ethylene-vinyl alcohol copolymer modified phenolic resin is pyrolyzed at high temperature, and the injected rare earth ions act as a catalytic promoter, further promoting the number of carbon nanotubes generated and improving the generation efficiency.

[0025] The active agent in the metallization slurry flows and migrates between the interface of the ceramic substrate and the metallization layer during the sintering process, which improves the wetting, increases the density, reduces the sintering temperature, accelerates the sintering process, and also plays a positive role in improving the bonding strength between the ceramic substrate and the metallization layer.

[0026] The tensile strength of the metallized layer of the metallized ceramic substrate prepared by the present invention reaches above 40 MPa, and has broad application prospects in the fields of LED heat dissipation substrates, ceramic packaging, electronic circuit substrates, semiconductor packaging, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the cross-sectional SEN diagram of the sample in Example 1 when the metallization layer is pulled off. DETAILED DESCRIPTION

[0028] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0029] Embodiment 1:

[0030] A preparation process of a metallized ceramic substrate:

[0031] S1: Add aluminum oxide and cobalt oxide in a mass ratio of 95:5 into a ball mill, use anhydrous ethanol as the ball milling medium, mix and ball mill on a planetary ball mill for 10 hours, and then dry to obtain a mixed powder. Weigh the following raw materials according to the following weight proportions: 56 parts of mixed powder, 1 part of dispersant triolein, 16 parts of ethanol, 16 parts of butanone, 5 parts of polyvinyl butyral, and 1 part of plasticizer DBP. 6 parts, first add the mixed powder, dispersant triolein, ethanol and butanone into a ball mill, use anhydrous ethanol as the ball milling medium, mix and ball mill on a planetary ball mill for 10 hours, then add polyvinyl butyral and plasticizer DBP, continue to mix and ball mill for 10 hours to obtain a casting slurry, vacuum defoam the casting slurry for 10 minutes, and then cast it on a casting machine, and form a wet blank of the required thickness by controlling the scraper, and then dry it to obtain a green blank, heat the green blank to 550℃ at a speed of 1℃ / min to debind for 2 hours, and then heat it to 1550℃ at a speed of 10℃ / min and sinter it for 4 hours to obtain a ceramic substrate, and finally fix the obtained ceramic substrate on an ion implanter, and evenly implant lanthanum ions on its surface, with an implantation dose of 5×10 17 ions / cm 2 The vacuum chamber of the ion implanter is maintained at 10 -3 -10 -4Pa, the ceramic substrate needs to be carefully cleaned and dried with acetone and anhydrous alcohol before ion implantation;

[0032] S2: 12.2 g of ethylene-vinyl alcohol copolymer was dissolved in 188 g of 50% phenol aqueous solution, and 122 g of 37% formaldehyde solution and 0.01g sodium hydroxide are mixed and then heated to 60°C and stirred for reaction for 5h. After the reaction is completed, the small molecules are removed by reduced pressure distillation to obtain ethylene-vinyl alcohol copolymer modified phenolic resin to prepare a metallization slurry. The metallization slurry includes the following components by mass percentage: 8% ethylene-vinyl alcohol copolymer modified phenolic resin, 2% ethyl cellulose, 40% molybdenum powder, 8% manganese powder, 3% calcium oxide, 3% lanthanum oxide, 3% silicon dioxide, 3% titanium dioxide, and the balance is pine oil. Molybdenum powder, manganese powder, calcium oxide, lanthanum oxide, silicon dioxide, and titanium dioxide are added to a ball mill, and dry powder ball milled on a planetary ball mill for 36h. The obtained mixture is mixed with ethylene-vinyl alcohol copolymer modified phenolic resin, ethyl cellulose, and pine oil and stirred for 1h. After completion, it is put into a vibration mill and vibrated for 4h. Finally, it is filtered with a 400-mesh nylon screen to obtain a metallization slurry;

[0033] S3: Print the metallization slurry on the surface of the ceramic substrate by a screen printer and dry it at 100°C. Control the thickness of the metallization layer after drying to be 10±0.5μm. Then heat it to 600°C at a rate of 1°C / min and keep it for 5h. Finally, heat it to 1350°C at a rate of 10°C / min and sinter it for 2h.

[0034] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed to the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine at a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 57MPa, see Figure 1 , carbon nanotubes can be seen in the cross section of the metallization layer.

[0035] Embodiment 2:

[0036] It is basically the same as Example 1, except that, in terms of mass percentage, the metallization slurry includes the following components: 10% ethylene-vinyl alcohol copolymer modified phenolic resin, 1% ethyl cellulose, 45% molybdenum powder, 8% manganese powder, 3% calcium oxide, 3% lanthanum oxide, 3% silicon dioxide, 3% titanium dioxide, and the balance is pinene alcohol.

[0037] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed in the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine with a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 54MPa.

[0038] Embodiment 3:

[0039] It is basically the same as Example 1, except that, in terms of mass percentage, the metallization slurry includes the following components: 5% ethylene-vinyl alcohol copolymer modified phenolic resin, 3% ethyl cellulose, 35% molybdenum powder, 12% manganese powder, 3% calcium oxide, 3% lanthanum oxide, 3% silicon dioxide, 3% titanium dioxide, and the balance is pinene alcohol.

[0040] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed in the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine with a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 49MPa.

[0041] Embodiment 4:

[0042] The method is basically the same as Example 1, except that cerium ion implantation is used instead of lanthanum ion implantation.

[0043] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed in the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine with a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 44MPa.

[0044] Comparative Example 1:

[0045] The method is basically the same as Example 1, except that the ceramic substrate is not subjected to lanthanum ion implantation during preparation.

[0046] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed in the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine with a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 41MPa.

[0047] Comparative Example 2:

[0048] The method is basically the same as Example 1, except that no cobalt oxide is added during the preparation of the ceramic substrate.

[0049] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed in the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine with a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 34MPa.

[0050] Comparative Example 3:

[0051] The method is basically the same as Example 1, except that polyvinyl butyral is used instead of the ethylene-vinyl alcohol copolymer modified phenolic resin.

[0052] A 4J33 kovar rod (rod body φ5mm, welding end φ3mm) was vertically brazed in the center of the metallized layer prepared in this embodiment to obtain a test piece. The solder was Ag72Cu28 solder sheet. The test piece was stretched using a WP500 tensile testing machine with a stretching rate of 5mm / min. The pull-off force when the sample was pulled off was converted into bonding strength. The tensile strength of the metallized layer was 30MPa.

[0053] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for preparing a metallized ceramic substrate, characterized in that: The details are as follows: S1: preparing a ceramic substrate containing a transition metal oxide; S2: preparing a metallization slurry containing ethylene-vinyl alcohol copolymer modified phenolic resin; S3: Printing or coating the metallization slurry on the surface of the ceramic substrate, followed by drying and sintering.

2. The process for preparing a metallized ceramic substrate according to claim 1, characterized in that: The ceramic substrate is also implanted with rare earth ions.

3. The process for preparing the metallized ceramic substrate according to claim 2, characterized in that: The rare earth ions are lanthanum ions and / or cerium ions.

4. The process for preparing a metallized ceramic substrate according to claim 2, characterized in that: The transition metal oxide in S1 is any one or more combinations of nickel oxide, cobalt oxide, iron oxide or zinc oxide.

5. The process for preparing a metallized ceramic substrate according to claim 2, characterized in that: The preparation method of the ethylene-vinyl alcohol copolymer modified phenolic resin described in S2 is as follows: Dissolve ethylene-vinyl alcohol copolymer in phenol aqueous solution, add formaldehyde and sodium hydroxide, stir to react for 1-5 hours, and then distill under reduced pressure to remove small molecules.

6. The process for preparing a metallized ceramic substrate according to claim 5, characterized in that: The reaction temperature is 50-70°C.

7. The process for preparing a metallized ceramic substrate according to claim 2, characterized in that: S1 is as follows: Alumina and transition metal oxides in a mass ratio of 80-100:1-5 are mixed and ball-milled and then dried to obtain a mixed powder, a green body is obtained by a tape casting method, the green body is debinded and sintered to obtain a ceramic substrate, and finally the ceramic substrate is implanted with rare earth ions.

8. The process for preparing a metallized ceramic substrate according to claim 1, characterized in that: The metallization paste comprises the following components in percentage by mass: 5-10% of ethylene-vinyl alcohol copolymer modified phenolic resin, 1-3% of ethyl cellulose, 35-45% of molybdenum powder, 8-12% of manganese powder, 10-15% of active agent, and the balance is pinene alcohol.

9. The process for preparing a metallized ceramic substrate according to claim 8, characterized in that: The active agent includes calcium oxide, lanthanum oxide, silicon dioxide and titanium dioxide; The mass ratio of the calcium oxide, lanthanum oxide, silicon dioxide and titanium dioxide is 1-5:1-5:1-5:1-5.

10. The process for preparing a metallized ceramic substrate according to claim 1, characterized in that: The sintering temperature in S3 is ≥1200°C.

Citation Information

Patent Citations

  • Preparation method for bending-resistant polyamide resin for automotive interior

    CN109135263A

  • Aluminum oxide ceramic surface metallization method

    CN114988918A

  • Metallized ceramic for new energy automobile

    CN116854502A

  • Glass fiber reinforced plastic and preparation method thereof

    CN118165440A

  • Ceramic metallization paste and preparation method thereof

    CN118180378A